The relationship between sedentary lifestyle, neck disability, and high blood pressure among bankers - Ida Ayu Indah Pradnyadewi; Ari Wibawa; Anak Agung Gede Angga Puspa Negara (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: A sedentary lifestyle greatly affects a person's life. Inactive lifestyle changes can result in increased neck disability. Sedentary behavior can also affect vascular, metabolic, and autonomic systems. This study aimed to determine the relationship between a sedentary lifestyle, neck disability, and high blood pressure in bank employees. Methods: The research method used is an observational analytical study with a cross-sectional approach and a sampling technique, namely purposive sampling. The number of samples obtained was 93 samples aged 18-55 years. The independent variable measured was sedentary lifestyle using the International Physical Activity Questionnaire (IPAQ) questionnaire. The dependent variables measured were neck disability using the Neck Disability Index (NDI) questionnaire and high blood pressure measured using a sphygmomanometer. Results: Based on the non-parametric Spearman Rho test, a value of p = 0.001 (p < 0.05) was obtained, which showed that there was a significant relationship between a sedentary lifestyle and neck disability and high blood pressure and the value of the correlation coefficient ranging from r = -0.831 to -0.928 and negative values indicating an undirected relationship with a very high level of correlation. Based on the results of multivariate analysis with regression logistic tests showed a significant relationship between a sedentary lifestyle and neck disability and high blood pressure characterized by p values < 0.05. Conclusion: Based on the study's results, there is a negative relationship between a sedentary lifestyle and neck disability and high blood pressure in bank employees. When a sedentary lifestyle shows low measurement results, it will indicate that the individual has a neck disability and high blood pressure.